Open source web content management systems analysis: the use of server resources - Andziulienė, Beatričė; Narbutas, Povilas (Lietuvos matematikos rinkinys, 2010)
Give general the most appropriate content management system selection stages of the process, divided into five phases. The last stage of the selection proposed by the Web content management system effectiveness analysis. The analysis of Drupal, Joomla!, Xoops content management systems, efficient use of server resources in three cases: the generation of dynamic pages, cache page and cache page with data compression. Content management systems are compared using the following criteria: the maximum number of queries per second, queries pending, RAM usage, CPU load, database management system load. It was found most effective resources of a server using a Web content management system.
Keywords: Content Management System (CMS); database management system; efficiency